Pitching Biomechanics and Shoulder Function in Baseball Pitchers with Scapular Dyskinesis - Huang, Tsun-Shun; Weng, Yi-Hsuan; Chang, Che-Chia; Tsai, Yung-Shen; Lin, Jiu-jenq (International Journal of Sports Medicine, 2023)
The primary purpose was to investigate the influence of scapular dyskinesis (SD) on pitching biomechanics and shoulder function in high school baseball pitchers. The secondary purpose was to identify possible factors associated with shoulder function in pitchers with SD. Thirty-eight pitchers were classified into the SD group (n=26) or the non-SD group (n=12). They were evaluated with the Kerlan-Jobe Orthopaedic Clinic shoulder and elbow (KJOC) scale and clinical measurements of shoulder characteristics, and with measurements of scapular kinematics, muscle activation, and ball speed during fastball pitching. Compared to the controls, the pitchers with SD had less scapular external rotation (difference=11.3 degrees, ES=0.92, p=0.012) during overall pitching and less upper trapezius (UT) activation during the late cocking (difference=7.1%, ES=0.79, p=0.019) and acceleration phases (difference=12.5%, ES=0.75, p=0.035). Higher UT activation during the late cocking phase was significantly associated with higher KJOC scores (standardized β=0.415, p=0.039). In conclusion, deficits in scapular external rotation and decreased UT activation during pitching were found in pitchers with SD. Higher UT activation may be important for shoulder function in pitchers with SD.
Keywords: kinematics; muscle activation; regression; performance